Feed Efficiency is Better and Activity is Greater in Growing Cattle Limit-Fed a High-Energy Diet During the Growing Phase Compared to a Traditional Roughage-Based Diet Fed for Ad Libitum Intake - M. A. Scilacci; E. C. Titgemeyer; S. P. Montgomery; T. J. Spore; A. J. Tarpoff; T. G. O'Quinn; W. R. Hollenbeck; D. A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2022)
The objective of this experiment was to compare performance impacts of a high-energy diet limit-fed at 2.2% of body weight (BW) daily on a dry matter (DM) basis to a traditional roughage-based diet fed forad libitumintake during the growing phase. Study Description:Three hundred seventy crossbred heifers (initial BW = 496 ± 44 lb) were used in a receiving and growing study at the Kansas State University Beef Stocker Unit in the spring of 2020. Animals were fed once daily at 7:00 a.m. Bunks were visually observed, and feed refused was estimated.Ad libitumfeed refusal was targeted at 20 lb. A pen scale was used to measure weekly pen BW, adjust feed offerings, and to calculate pen performance. The Bottom Line:Growing heifers limit-fed a high-energy diet at 2.2% of BW daily on a DM basis had 35% better feed efficiency and were more active by 23 minutes per day, on average, than heifers full-fed a traditional roughage-based diet.
Keywords: Limit feeding; growing cattle; growth performance